1982
DOI: 10.3168/jds.s0022-0302(82)82338-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum and Pulsation Ratio on Udder Health

Abstract: Effects of vacuum and pulsation ratio on udder health were studied for 36 first parity animals in a 60-day trial. Treatments consisted of vacuum at 33.3, 41.6, and 50 kPa at pulsation ratios of 50:50, 60:40, and 70:30 at 60 pulsations per min. All teats were exposed to a culture broth of Staphylococcus aureus after machine removal. Numbers of intramammary infections and somatic cells were determined. Analysis for number of intramammary infections indicated no significant differences among treatments for number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
2
14
1
3
Order By: Relevance
“…For Manchega ewes, Fernández et al (1999) found that SCC as well as udder health were influenced to a significant degree by the combination of high vacuum (42 kPa), with 120 pulsations/min, compared to the lower level of vacuum (36 kPa), with 120 or 180 pulsations/min. Similar results were observed in cows (Mahle et al, 1982) and in local Greek goats as the vacuum level increased from 36 to 44 and 52 kPa (Sinapis and Vlachos, 1999). This is in contrast with findings for Manchega ewes (Peris et al, 2003) where the SCC was not affected by vacuum level (36 and 42 kPa).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For Manchega ewes, Fernández et al (1999) found that SCC as well as udder health were influenced to a significant degree by the combination of high vacuum (42 kPa), with 120 pulsations/min, compared to the lower level of vacuum (36 kPa), with 120 or 180 pulsations/min. Similar results were observed in cows (Mahle et al, 1982) and in local Greek goats as the vacuum level increased from 36 to 44 and 52 kPa (Sinapis and Vlachos, 1999). This is in contrast with findings for Manchega ewes (Peris et al, 2003) where the SCC was not affected by vacuum level (36 and 42 kPa).…”
Section: Discussionsupporting
confidence: 86%
“…For Manchega ewes Fernández et al (1999) found that the SCC as well as the udder health were significantly influenced when a high vacuum of 42 kPa was applied, compared to a lower level of vacuum (36 kPa). Similar results were observed in cows (Mahle et al, 1982) and also in dairy goats (Sinapis and Vlachos, 1999). It is probable that the increase of SCC is due to the higher vacuum level, but this has yet to be proven.…”
Section: Introductionsupporting
confidence: 90%
“…Quarter-individual milking and udder health front quarters (Reitsma et al 1981) and the number of infected quarters increased as vacuum increased from 33·3 to 50 kPa (Mahle et al 1982). These results could not be verified by our own investigations.…”
Section: Effects On Quarter Health Statuscontrasting
confidence: 77%
“…The increase came suddenly and was synchronized with the onset of automatic milking; but the number of cows with increased SCC decreased slowly 3 months after the new installation (Rasmussen et al 2001). Reitsma et al (1981) described how the duration of the liner closure per pulsation cycle affected bovine mastitis and noticed that the occurrence of new IMI increased considerably with a decrease in duration of liner closure, especially at the pulsation ratio 70 : 30 (Mahle et al 1982). They also found out that rear quarters were infected more readily than Table 3)…”
Section: Effects On Quarter Health Statusmentioning
confidence: 95%
“…() report that the occurrence of mastitis is associated with liner slip, Mahle et al . () reported an association with set operating vacuum and pulsation function, and Natzke et al . () report an association with the milking times.…”
Section: Introductionmentioning
confidence: 94%